Kantianism, Liberalism, and Feminism - Hay, C. author. aut Link
XIII, 202 p.
Keywords: In this book Hay argues that the moral and political frameworks of Kantianism and liberalism are indispensable for addressing the concerns of contemporary feminism. After defending the use of these frameworks for feminist purposes, Hay uses them to argue that people who are oppressed have an obligation to themselves to resist their own oppression.